Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1021/bc034179p
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Corroles Bind Tightly to Human Serum Albumin

Abstract: Amphiphilic 2,17-bis-sulfonato-5,10,15(trispentafluorophenyl)corrole (2) and its Ga and Mn complexes (2-Ga and 2-Mn) form tightly bound noncovalent conjugates with human serum albumin (HSA). Protein-induced changes in the electronic absorption, emission, and circular dichroism spectra of these corroles, as well as results obtained from HPLC profiles of the conjugates and selective fluorescence quenching of the single HSA tryptophan, are interpreted in terms of multiple corrole:HSA binding sites. High-affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
106
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(111 citation statements)
references
References 45 publications
5
106
0
Order By: Relevance
“…In contrast, the inability of corroles to penetrate cell membranes without a carrier protein can avoid such detrimental side effects, should the corrole release prematurely from the carrier before reaching a target cell. This is an unlikely possibility, however, due to the high degree of binding stability to endure ultrafiltration, HPLC, and nonexchange with serum protein (5,6). Our studies here further confirm that the targeted complex retains integrity in human serum, localizes tumors in vivo, and elicits tumor cell death while sparing healthy tissue such as the heart.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In contrast, the inability of corroles to penetrate cell membranes without a carrier protein can avoid such detrimental side effects, should the corrole release prematurely from the carrier before reaching a target cell. This is an unlikely possibility, however, due to the high degree of binding stability to endure ultrafiltration, HPLC, and nonexchange with serum protein (5,6). Our studies here further confirm that the targeted complex retains integrity in human serum, localizes tumors in vivo, and elicits tumor cell death while sparing healthy tissue such as the heart.…”
Section: Discussionsupporting
confidence: 68%
“…Specifically, these corroles are water soluble (thus enabling facile use in physiological fluids), do not require photoexcitation to elicit cytotoxicity (thus expanding the potential tissue depth and distance at which corrole-mediated therapy may be administered), are unable to enter cells without the aid of a carrier molecule (thus aiding the specificity of delivery), and bind to cell-targeting proteins in a very tight, spontaneous and noncovalent fashion (4,5). Accordingly, we have explored the possibility of assembling targeted corrole complexes with modified cell targeting ligands previously studied for tumor-targeted cell penetration (6,7).…”
mentioning
confidence: 99%
“…14 Here we report a water-soluble gold(III) complex of 2,17-bissulfonato-5,10,15-trispentafluorophenylcorrole (1-Au): we have studied its association with human serum albumin (HSA), the most abundant (and potential drug transporting) protein present in plasma. 15 In the course of our investigations, we found 1-Au to be cytotoxic and cytostatic to cisplatin-resistant cancer cell lines.…”
mentioning
confidence: 72%
“…24 No change in the shape of the signal accompanied View Article Online the titration, quite unlike our observations in related CD experiments where we found that 8-10 equivalents of 1-Ga bind to HSA. 15 Additional evidence for marked differences in binding affinities of the two corroles was obtained upon quenching of the fluorescence of the only tryptophan residue present in HSA by 1-Au and 1-Ga (Fig. 4a and b, respectively).…”
mentioning
confidence: 82%
“…The presence of an induced circular dichroism signal suggests that the metal is incorporated in a well-defined chiral environment, [37,39] consistently with the structurally characterized hemin&HSA conjugate.…”
Section: Supramolecular Anchoring Strategiesmentioning
confidence: 57%